Perspectives of Teachers on Autism Spectrum Disorders (ASD) in Nepal - Shrestha, Sharan Hari (Interdisciplinary Research in Education, 2019)
This study aimed to explore the knowledge, awareness, and attitude of teachers regarding ASD and educating children with ASD. The research was conducted through a quantitative method utilizing a survey design in this study. Seventy-six teachers from seven special and twelve integrated schools from Kathmandu valley were selected through purposive sampling method. A Likert Scale with a 5-point survey instrument (questionnaire) was created and implemented. The data from the questionnaire were analyzed with descriptive statistics. The result of this study demonstrated that teachers of Nepal have the general idea of ASD but they don't possess in-depth knowledge regarding ASD. In this study, most of the teachers thought that students with ASD should be placed in a special education classroom rather than a general and inclusive classroom. Moreover, Nepalese teachers don’t think they are prepared to educate students with ASD in their classes and also claimed teachers need additional training, seminar and workshop concerning ASD. Furthermore, the teachers of Nepal have limited knowledge, awareness, understanding, attitudes, placement services, and teaching readiness towards ASD. However, they have the basic knowledge and understanding of ASD.